Pemetaan Tiga Dimensi Gua Aul Di Desa Cikupa-Ciamis, Jawa Barat Menggunakan Terrestrial Laser Scanner (TLS) - Ayu Theodolita, Ananda Jessyca; Gusti Ayu Jessy Kartini; Lutfi Yondri (PURBAWIDYA, 2025)
This study examines the potential of Terrestrial Laser Scanner (TLS) technology in documenting and understanding the characteristics of cave spaces as part of geospatial and cultural heritage. The study was conducted in Aul Cave, West Java, as part of efforts to preserve and interpret underground spaces through a digital spatial approach. Using the Trimble X7 TLS, this research produced a comprehensive three-dimensional representation of the cave structure, including its geometric shape and surface characteristics. The analysis focused on the differences in material properties between natural elements such as stalactites and rock walls, and artificial materials such as cement and paving blocks, based on laser reflection intensity values. Through this approach, the study not only provides precise visual documentation but also opens up possibilities for interpreting the function of cave spaces and indications of past human activity. The results of the study show that TLS is not only effective as a documentation tool but also relevant as a spatial analysis method in archaeological, geospatial, and cultural heritage preservation studies. This approach is expected to encourage broader utilization of digital technology in spatial-based research and the preservation of underground cultural heritage.